Effect of demolished concrete and stone crusher dust on properties of M−40 grade paver blocks. (2021) - Kumar Attri, Gyanendra; Gupta, R.C.; Shrivastava, Sandeep
Abstract: Construction & demolition waste (C&DW) management is a major concern because of the rate of generation and associated environmental impacts. Utilization of stone crusher dust (SCD) is also a challenge for the stone crusher owners. So, this study utilized C&DW and SCD in paver block manufacturing. Mechanical & durability performance i.e. density, compressive strength, split tensile strength, water absorption, abrasion resistance & ultrasonic pulse velocity were evaluated. Results suggest that C&DW & SCD may replace up to 45% natural coarse aggregate & up to 100% river sand. This will produce cost effective concrete mix for paver blocks. Research findings may help government agencies to frame guidelines for effective utilization of C&DW and SCD.